The PARADOX OF STATE OF LAW IDEA ON PANCASILA PHILOSOPHICAL JUSTIFICATION AS SOURCES OF LAW: Paradoks Ide Negara Hukum dalam Justifikasi Filosofis Pancasila sebagai Sumber Hukum - Silalahi, Artha Debora (Jurnal Konstitusi, 2024)
The state of law idea formulated in the provisions of Article 1 paragraph (3) of the 1945 Constitution of the Republic of Indonesia is a formulation containing normative statements that is still dubious and seems convincing. The Pancasila philosophical justification as the source of legal norms needs to be questioned. The possibility if Pancasila is used as the source of law will expand coercive actions and choices of legal imperatives. The research method used is analytical techniques with a critical-philosophical approach, which brings factual concepts closer by resting on philosophical issues within the scope of concepts and values for understanding Pancasila which is still interpreted as the source of all sources of law. The research findings found that the construction of the state of law idea should not depend on legal rigidity. It must be able to be created as a discursive space that is truly interpretive and not limitative. The paradox’s problem can be raised through legal interpretations which are able to find a relationship between what should be normative and what is factual.